CAPAIAN MILLENNIUM DEVELOPMENT GOALS (MDG’S) BERKAITAN DENGAN KESEHATAN ANAK DAN IBU DI PROVINSI RIAU - Yoppy Listi; Yusbar Yusuf; Rahmita Budiartiningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in Riau Province in October to December 2014. The purpose of this study was to determine how the achievement of the MDG's related to child and maternal health in the province of Riau, using secondary data analyzed descriptively. MDG's is an attempt to meet the basic rights of human needs. The millennium development vision is to promote human development as the key to achieving social and economic development sustainable. MDG's have 8 indicators, wherein each of the indicators has the achievement of targets in 2015. The results in the field of child health is to lower the infant mortality rate per 1,000 live births in the province of Riau already above the limit of the MDG's are 9 infant deaths per 1,000 live births by MDG's are 23 deaths per 1,000 live births. For the reduction of child mortality rate per 1,000 live births Riau province is under the limit is 5 infant deaths per 1,000 live births. For reducing maternal mortality by three-quarters of Riau Province will reach the target in 2015. As for the scope of maternal outcomes attended by health personnel in Riau Province has almost reached the target of MDG's in 2013. The percentage of married women aged 15-49 years are still resulted in significant progress is slow.Keywords : Achievement MDG’s, Child and Maternal Mortality Rates, Live Births, and Contraception